Paradigm of defence and security regulation development in European Union - Muravska (Yakubivska), Yulia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the investigation of the paradigm of defence and security regulation development in European Union. The organizations responsible for the safety of those societies technologically advanced in the last two periods in the European Union. Ukraine is actively strengthening its position in the context of euroinegration to EU structures. The European Union undertakes extra tasks in relation to military actions run by NATO and United Nations. The institutional defense and security providing of the EU is analyzed in the article. The conclusions about current state and efficiency level of defense and security state and legal regulation in the European Union are formed.